Optimal placement of the phasor measurement units using differential evolution algorithm - Mahmoud Zadehbagheri; Alireza Abbasi; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The increasing consumption of the electric energy aimed at develop the transmission networks and the demand for higher reliability from the network; in this regard, wide-area measurement systems using phasor measurement units (PMUs) have revolved the trend of power network management. In this paper, the optimal allocation of PMUs in order to reach the perfect observability of the network; based on a differential evolution algorithm, is proposed and it is shown that, the deployment of constraints related to the zero-injection busses (ZIB) aimed to decrease the number of PMUs and their corresponding cost. By comparing the proposed method to the other methods, its simplicity and good performance are approved.